2020
DOI: 10.1002/hep4.1488
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Protein Arginine Methyltransferase 1 Suppresses Alcohol‐Induced Hepatocellular Carcinoma Formation by Inhibition of Inducible Nitric Oxide Synthase

Abstract: Alcohol is a well-established risk factor for hepatocellular carcinoma (HCC), but the mechanisms by which alcohol promotes liver cancer are not well understood. Studies suggest that ethanol may enhance tumor progression by increasing hepatocyte proliferation and through alcohol-induced liver inflammation. Protein arginine methyltransferase 1 (PRMT1) is the main enzyme responsible for cellular arginine methylation. Asymmetric dimethyl arginine, produced by PRMT1, is a potent inhibitor of nitric oxide synthases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…Given that the amino acid sequences of human and mouse PRMT1 proteins share 99% identity and the expression level of PRMT1 and PGC-1α negatively correlated with liver fat content are conserved between human and mouse, we expect the underlying regulatory mechanism is similar. Interestingly, recent studies reported that PRMT1 could protect alcohol-induced liver injury and suppress alcohol‐induced hepatocellular carcinoma formation in mice 25 , 26 . We also observed that the expression level of the liver injury markers ALT and AST were higher in obese humans with low hepatic PRMT1 expression ( Table S1 , P = 0.07 for ALT and P = 0.08 for AST).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the amino acid sequences of human and mouse PRMT1 proteins share 99% identity and the expression level of PRMT1 and PGC-1α negatively correlated with liver fat content are conserved between human and mouse, we expect the underlying regulatory mechanism is similar. Interestingly, recent studies reported that PRMT1 could protect alcohol-induced liver injury and suppress alcohol‐induced hepatocellular carcinoma formation in mice 25 , 26 . We also observed that the expression level of the liver injury markers ALT and AST were higher in obese humans with low hepatic PRMT1 expression ( Table S1 , P = 0.07 for ALT and P = 0.08 for AST).…”
Section: Discussionmentioning
confidence: 99%
“…It is a paradox that recent studies reported the protective effects of hepatic PRMT1 in alcohol-induced inflammation 25 and hepatocellular carcinoma 26 . The potential side effects of targeting hepatic PRMT1 on liver remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression of PRMT1 has been implicated in the tumorigenesis of multiple cancers including progesterone receptor positive breast cancer, hepatocellular carcinoma (HCC), neuroblastoma, and pancreatic cancer [ 35 , 36 , 37 , 38 ]. PRMT1 is also a known contributor to the development of glioblastoma (GBM) [ 15 , 39 ].…”
Section: Functional Significance Of Arginine Methylationmentioning
confidence: 99%
“…Several previous studies have revealed the roles that PRMTs play in HCC. PRMT1 inhibition results in reduced HNF4α expression and hepatocyte proliferation, thus promoting alcohol-induced HCC progression, which suggests that PRMT1 seems to perform a protective role in the context of alcohol-induced HCC [ 52 , 53 , 31] . Nevertheless, PRMT1 functions as an oncogene in other contexts of HCC.…”
Section: The Role Of Prmts In Hcc Malignant Phenotypesmentioning
confidence: 99%